Analysis of the Causes of the Increase in Reading Interest of Students at SD Negeri 2 Lamangga - Agusalim (AIQU: Journal Multidiscipliner of Science, 2025)
This study aims to identify factors that influence the reading interest of fourth-grade students at SD Negeri 2 Lamangga in the digital era and to formulate relevant and applicable solutions to improve literacy culture among students. A qualitative approach was used with a case study design, where data were collected through observation, in-depth interviews with teachers and parents. The results of the study indicate that students' reading interest is still relatively low, which is caused by several main factors, including the limited collection of books in the school library that are less interesting and less suited to children's interests, the dominance of the use of digital technology for entertainment such as games and videos, minimal parental involvement in accompanying children to read at home, and literacy learning strategies in the classroom that are still monotonous and have not utilized digital media optimally. To overcome these problems, this study recommends four main solutions: (1) developing a more diverse book collection that suits students' interests, (2) integrating digital technology such as e-book and audiobook applications into literacy activities, (3) involving parents through family literacy programs, and (4) implementing innovative and interactive learning strategies in the classroom. It is hoped that by implementing this approach, students' interest in reading can be increased sustainably and literacy activities can become a fun and meaningful part of students' learning lives in the digital era.